Odpowiedź :
[tex]1,k,l,m[/tex] - pierwiastki wielomianu
[tex]w(x)=x^4+ax^3+bx^2+cx+d[/tex]
[tex]w(x)=(x-1)(x-k)(x-l)(x-m)[/tex]
1.
[tex]1+k+l+m=5[/tex]
[tex]k+l+m=5-1[/tex]
[tex]k+l+m=4[/tex]
2.
[tex]1\cdot k l m=-6[/tex]
[tex]k l m=-6[/tex]
3.
[tex]w(-2)=60[/tex]
[tex](-2-1)\cdot(-2-k)\cdot(-2-l)\cdot(-2-m)=60 [/tex]
[tex]-3(4+2l+2k+kl)(-2-m)=60\ \ \ |:(-3) [/tex]
[tex]-8-4m-4l-2lm-4k-2km-2kl-klm=-20\ \ \ |:(-1) [/tex]
[tex] 8+4m+4l+2lm+4k+2km+2kl+klm=20[/tex]
[tex]8+4m+4l+2lm+4k+2km+2kl+klm=20[/tex]
[tex](4m+4l+4k)+2lm+2km+2kl+klm=20-8[/tex]
[tex]4(m+l+k)+2lm+2km+2kl-6=12[/tex]
[tex]4\cdot4+2lm+2km+2kl=12+6[/tex]
[tex]16+2lm+2km+2kl=18[/tex]
[tex]2lm+2km+2kl=18-16[/tex]
[tex]2lm+2km+2kl=2\ \ \ |:2[/tex]
[tex]lm+km+kl=1[/tex]
[tex]kl+km=1-lm[/tex]
=======================
[tex]k+l+m=4\ \ \ |\cdot k[/tex]
[tex]k^2+kl+km=4k[/tex]
[tex]k^2+1-lm=4k\ \ \ |\cdot k[/tex]
[tex]k^3+k-lkm=4k^2[/tex]
[tex]k^3+k-(-6)-4k^2=0[/tex]
[tex]k^3-4k^2+k+6=0[/tex]
[tex]-1[/tex] jest pierwiastkiem
(dzielenie w załączniku)
[tex](k^2-5k+6)(k+1)=0[/tex]
[tex](k^2-3k-2k+6)(k+1)=0[/tex]
[tex][k(k-3)-2(k-3)](k+1)=0[/tex]
[tex](k-3)(k-2)(k+1)=0[/tex]
[tex]k=-1\ \ \ lub\ \ \ k=2\ \ \ lub\ \ \ k=3[/tex]
---------------
[tex]k=-1[/tex]
[tex]-1+l+m=4[/tex]
[tex] l=4+1-m[/tex]
[tex] l=5-m[/tex]
[tex]k l m=-6[/tex]
[tex]- l m=-6[/tex]
[tex]-lm=-6[/tex]
[tex]-(5-m)m+6=0[/tex]
[tex]-5m+m^2+6=0[/tex]
[tex]m^2-5m+6=0[/tex]
[tex]m^2-3m-2m+6=0[/tex]
[tex]m(m-3)-2(m-3)=0[/tex]
[tex](m-3)(m-2)=0[/tex]
[tex]m=2\ \ \ lub\ \ \ m=3[/tex]
[tex]l=5-2=3\ \ \ lub\ \ \ l=5-3=2[/tex]
---------------
[tex]k=2[/tex]
[tex]2+l+m=4[/tex]
[tex] l=4-2-m[/tex]
[tex] l=2-m[/tex]
[tex]k l m=-6[/tex]
[tex]2l m=-6\ \ \ |:2[/tex]
[tex]lm=-3[/tex]
[tex](2-m)m+3=0[/tex]
[tex]2m-m^2+3=0[/tex]
[tex]-m^2+2m+3=0\ \ \ |:(-1)[/tex]
[tex]m^2-2m-3=0[/tex]
[tex]m^2+m-3m-3=0[/tex]
[tex]m(m+1)-3(m+1)=0[/tex]
[tex](m+1)(m-3)=0[/tex]
[tex]m=-1\ \ \ lub\ \ \ m=3[/tex]
[tex]l=2-(-1)=2+1=3\ \ \ lub\ \ \ l=2-3=-1[/tex]
---------------
[tex]k=3[/tex]
[tex]3+l+m=4[/tex]
[tex] l=4-3-m[/tex]
[tex] l=1-m[/tex]
[tex]k l m=-6[/tex]
[tex]3l m=-6\ \ \ |:3[/tex]
[tex]lm=-2[/tex]
[tex](1-m)m=-2[/tex]
[tex]m-m^2+2=0[/tex]
[tex]-m^2+m+2=0\ \ \ |:(-1)[/tex]
[tex]m^2-m-2=0[/tex]
[tex]m^2+m-2m-2=0[/tex]
[tex]m(m+1)-2(m+1)=0[/tex]
[tex](m+1)(m-2)=0[/tex]
[tex]m=-1\ \ \ lub\ \ \ m=2[/tex]
[tex]l=1-(-1)=1+1=2\ \ \ lub\ \ \ l=1-2=-1[/tex]
Pozostałe pierwiastki wielomianu to: [tex]-1,2,3[/tex]